2000
DOI: 10.1046/j.1365-2923.2000.00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of intern attendance at a seminar-based training programme: a behavioural intention model

Abstract: The establishment of resident education programmes within teaching hospitals requires attention to and modification of facilitating conditions that may allow improvements in attendance and in quality of the programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…Previous studies have shown that self-reporting may overestimate the real attendance as measured by sign-in logs. 15 Actual staff attendance therefore may be even lower than reported in our study, further emphasizing the need to address factors affecting attendance. The open-ended question format used for much of the survey may have permitted faculty to overlook important answers.…”
Section: Limitationscontrasting
confidence: 55%
“…Previous studies have shown that self-reporting may overestimate the real attendance as measured by sign-in logs. 15 Actual staff attendance therefore may be even lower than reported in our study, further emphasizing the need to address factors affecting attendance. The open-ended question format used for much of the survey may have permitted faculty to overlook important answers.…”
Section: Limitationscontrasting
confidence: 55%
“…This theoretical framework provides a way to overcome most of the criticism directed at rational choice theory, offering a comprehensive heuristic as well as a model for empirical analysis of the "strengths and weaknesses of different component factors in different kinds situations" (Jackson 2004). TIB has been applied to various issues, including environmentally relevant behaviour (Thompson et al, 1991;Boots and Treolar, 2000;Bamberg and Schmidt, 2003;Gagnon et al, 2003) and has generally shown a higher explanatory power than competing behavioural theories. In addition, TIB is more comprehensive than other theories (Jackson, 2004) in that it includes a wide array of potentially relevant drivers, which makes it appropriate to the integrative investigation of agents' behaviour in complex systems, as called for, for example, by Scoones et al (2007) and, with specific reference to farmers' decision-making, by Edwards-Jones (2006).…”
Section: Theory Of Interpersonal Behaviour Triandis' Theory Of Intermentioning
confidence: 99%
“…[10][11][12] Stress, fatigue, sleep deprivation, and ''burnout'' have been found to impair learning and performance, 13,14 and only about half of residents attend didactic teaching conferences, with fewer still reporting they remain alert throughout. 15,16 Our own previous 1989 national, multi-specialty survey found that, although quantity and quality of time with attending physicians was most valued by residents, they also ranked ''other residents'' and ''special patients'' as additional important sources of learning. 8 Positive factors contributing to satisfaction with their internship year were, in order, attending physicians, other residents, patient rounds, seminars, and time with attending physicians.…”
Section: Introductionmentioning
confidence: 99%